Internet econometrics - Allegrezza, Serge, 1959-; Dubrocard, Anne (Applied Econometrics Association series, 2012)
The rise of information technologies and the proliferation of internet based communication has often been referred to as the fourth technological revolution. Just like steam and electricity, the diffusion of these new technologies has radically altered products and the organisation of industrial production, ushering in a new era. This book employs a variety of tools and methodologies in order to quantify the impact of new developments in ICT, examining data at both micro and macro levels. A comparative analysis of a range of countries provides a comprehensive account of the new organisational frontiers and business models that ICT has generated.